Strategi Pemberdayaan Sumber Daya Manusia di MTs Nurul Huda Sedati Sidoarjo - Fairuz Bilah Izzah Hazwani (Program Studi Manajemen Pendidikan Islam UIN Sunan Ampel Surabaya, 2022)
Competition in the world of education that is getting tighter has resulted in several educational institutions being abandoned by their customers, resulting in a merger between educational institutions, with conditions like this, educational institutions must make breakthroughs and innovations to maintain the existence of the educational institutions they manage and to face the competitive climate through empowerment. human resources in a well-planned manner. In the scope of education, strategy is the most concern for achieving madrasa goals. One of the strategies or efforts that can be done to maintain the existence of madrasas is through the empowerment of human resources. In this case, human resources are the key to success in formulating a good strategy. Therefore, the organization's strategic plan must be systematically prepared. The Human Resources Empowerment Strategy aims to create human resources (teachers, employees and related stakeholders) who have competence in their fields of expertise, authority, and responsibility. This study aims to describe the strategy of empowering human resources in Madrasah Tsanawiyah Nurul Huda Sedati, Sidoarjo. This study uses a qualitative research approach, the type of descriptive research with data collection techniques of observation, interviews and documentation. The data analysis process uses data reduction, data presentation and conclusion drawing. As well as the validity of the data using source triangulation The results of this study explain that the empowerment of human resources is carried out through the following processes: (1) determining human resource needs (2) selecting human resources to be empowered (3) making clear configurations and rules (4) implementing, guidance or workshops (5 ) provide encouragement and motivation to always develop. Keywords: Strategy, Human Resource Empowerment